2015
DOI: 10.1162/jocn_a_00695
|View full text |Cite
|
Sign up to set email alerts
|

Motivationally Significant Self-control: Enhanced Action Withholding Involves the Right Inferior Frontal Junction

Abstract: In everyday life, people use self-control to withhold actions. This ability is particularly important when the consequences of action withholding have an impact on the individual's well-being. Despite its importance, it is unclear as to how the neural nodes implicated in action withholding contribute to this real-world type of self-control. By modifying an action withholding paradigm, the go/no-go task, we examined how the brain exerts self-control during a scenario in which the implications of withholding an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Although the corresponding response signal might provide a stronger source of evidence for behavior selection in this case, it would be evidence in favor of inhibiting the response rather than executing it. This would be consistent with how the motivational aspects of reward modulate inhibitory processing in a stop-signal task (Schevernels et al, 2015) and go/no-go task (O’Connor, Upton, Moore, & Hester, 2015). Participants had ample time to prepare how they would react to stimuli of a particular color upon seeing the color cue at the beginning of each trial, but were unable to engage inhibitory processes in accordance with task goals when the stimuli were previously associated with reward.…”
Section: Discussionsupporting
confidence: 73%
“…Although the corresponding response signal might provide a stronger source of evidence for behavior selection in this case, it would be evidence in favor of inhibiting the response rather than executing it. This would be consistent with how the motivational aspects of reward modulate inhibitory processing in a stop-signal task (Schevernels et al, 2015) and go/no-go task (O’Connor, Upton, Moore, & Hester, 2015). Participants had ample time to prepare how they would react to stimuli of a particular color upon seeing the color cue at the beginning of each trial, but were unable to engage inhibitory processes in accordance with task goals when the stimuli were previously associated with reward.…”
Section: Discussionsupporting
confidence: 73%
“…In brief, attention processing is a crucial factor in inhibition control, and the RR stimulus captures more attention, thus indirectly contributing to the enhancement of response inhibition. Based on this finding, we might conjecture that a dysfunction of inhibitory control may be compounded by other factors such as attentional capture rather than a dysfunction in motor inhibition per se (O'Connor et al , 2015). Indeed, recent computational work revealed that deficits characterized by response inhibition could be explained by factors such as motivation and attentional processing and their corresponding neural mechanisms (Wiecki and Frank, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…This finding is approximately consistent with a key role of the lateral PFC in conscious perception in humans (Dehaene et al, 2006;Brown et al, 2019) and monkeys (Panagiotaropoulos et al, 2012;van Vugt et al, 2018;Kapoor et al, 2020). However, it could also be associated with the role of the IFJ in cognitive control and task switching (Brass et al, 2005) and/or action withholding (O'Connor et al, 2015); whereas inattentionally blind subjects were not distracted from the dot task, aware subjects had to actively inhibit the irrelevant faces to perform the distractor task adequately. In fact, the unheralded faces may have acquired some implicit relevance (Block, 2019), since synchronized IFJ and FG activity has specifically been shown to represent object-based attention to faces (Baldauf and Desimone, 2014).…”
Section: Discussionmentioning
confidence: 99%